Effectiveness of Law Enforcement in Achieving Certainty and Justice - Diana Pujiningsih (Ipso Jure, 2026)
Law enforcement is a central instrument in realizing two fundamental legal values ​​that are often in tension with each other: legal certainty and substantive justice. This article aims to analyze the extent to which law enforcement in Indonesia is able to realize these two values ​​simultaneously, as well as the factors that influence its effectiveness. This study uses a normative legal research method with a conceptual and legislative approach, supported by secondary data in the form of laws and regulations, court decisions, and the latest legal literature. The results show that the effectiveness of law enforcement is greatly influenced by the quality of legal substance, the integrity and competence of law enforcement officers, the legal culture of the community, and the consistency of the application of legal principles in judicial practice. It was also found that an overly legalistic-positivistic orientation of law enforcement tends to produce formal legal certainty but ignores the community's sense of justice, while an approach that overly prioritizes substantive justice without a clear basis for legal certainty can lead to uncertainty and inconsistency in decisions. This article recommends the need for a progressive approach that integrates legal certainty and substantive justice through strengthening the judicial system, institutional reform, and strengthening the community's legal culture as prerequisites for realizing effective law enforcement